APLIKASI SINTESIS TiO2 NANOPARTIKEL DALAM DEGRADASI FOTOKATALITIK METIL JINGGA - Husna, Isramil; Umar, Akrajas Ali; Ramli, Muhammad Adam (Sainstek : Jurnal Sains dan Teknologi, 2018)
The development in textile industry results in the increase of the use of non-organic materials in human life, such as the use of dyes that cannot be decomposed naturally, such as the use of artificial dyes in textile industry and other similar fields. This implies that if those artificial dye are not carefully managed, they will have a definite impact on the environment, such as water pollution where those substances contaminate clean water and therefore will be very dangerous for human daily needs of water for drinking, bathing and other needs. This in turn will cause various diseases in living things and pollute nature as well. The purpose of this study is to figure out the effect of methyl orange degradation by the addition of TiO2 photocatalyst. In this study, 10 ppm orange methyl solution were used, where 5 ml of orange methyl were dissolved in 5 ml of water then added with TiO2 and then irradiated with UV for 180 minutes. By calculating the degradation of methyl orange every 10 minutes, which was measured using a UV-Vis spectrophotometer. The finding shows that the longer the irradiation takes place, the more desirable degradation of methyl orange is desired. The results obtained from 180 minutes are absorbance values that are worth 0.8 down to 0.3.